Effect on thermal and combustion behaviors of montmorillonite intercalation nickel compounds in polypropylene/IFR system. (17th November 2015) - Kong, Qinghong; Zhang, Hongkai; Zheng, Lu; Wang, De‐Yi; Zhang, Junhao
Abstract : A new montmorillonite intercalation nickel compound (MINC) was devised and synthesized. MINC was modified by cetyl trimethyl ammonium bromide to obtain organic MINC (OMINC). The results of X‐ray diffraction show that the layer spacing was expanded by nickel compound and cetyl trimethyl ammonium bromide, indicating that OMINC was prepared successfully. OMINC was further incorporated into polypropylene (PP)/intumescent flame retardant (IFR) system for preparing PP/IFR/OMINC nanocomposites via melt blending. In thermogravimetric analysis, PP/IFR/OMINC nanocomposites exhibit an enhanced thermal behavior and residue amount. Vertical burning test (UL‐94) and limited oxygen index results show that PP/IFR/OMINC nanocomposites have excellent flame retardance, i.e. the limited oxygen index value at 29.5 and UL‐94 V0 level for PP/IFR/4 wt% OMINC nanocomposites. According to cone calorimeter testing, the addition of OMINC brings an efficient reduction of flammability parameters, such as peak heat release rate, total heat release, and smoke production rate. Copyright © 2015 John Wiley & Sons, Ltd.